(untitled) - Gamota, George (Cambridge, Mass., 1988)
This is a guide to English-language sources providing information on recent technological developments in Japan. Historical ources are not included* Each description includes the author, title, place of publication, publisher, publication date, total number of pages and call number.
Keywords: Technology,Research, Industrial,Công nghệ,Nghiên cứu, công nghiệp; Japan,Japan,Nhật Bản,Nhật Bản